2021
DOI: 10.33215/sbr.v1i1.561
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Traditional Communication Channels on Customer Purchase Decision: A Case Study of University Students in Ghana

Abstract: Purpose- Marketers want to know the best advertisement medium which can make their advertising more effective. This study seeks to find a linkage between television advertisement, radio advertisement, newspaper advertisement, and outdoor advertisement towards customers’ purchase decisions in Ghana. Design/Methodology- Using University students in Ghana as a population, the study employed a simple random sampling approach and collected data from University students in UCC and KNUST. Seven hundred and fifty (750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In contrast, LM produced RMSE figures of 0.575, 0.668, 0.580, and 0.709, respectively, for the model estimation using PLS-RMSE. So, the negative values obtained in Table 10 after deducting the PLS-RMSE values from the LM-RMSE values indicated a high predictive power of the model, supporting those of Ahakwa et al (2021c), Quagraine et al (2021), and (Odai et al, 2021).…”
Section: Measurement Model Assessmentmentioning
confidence: 57%
See 1 more Smart Citation
“…In contrast, LM produced RMSE figures of 0.575, 0.668, 0.580, and 0.709, respectively, for the model estimation using PLS-RMSE. So, the negative values obtained in Table 10 after deducting the PLS-RMSE values from the LM-RMSE values indicated a high predictive power of the model, supporting those of Ahakwa et al (2021c), Quagraine et al (2021), and (Odai et al, 2021).…”
Section: Measurement Model Assessmentmentioning
confidence: 57%
“…Therefore, if all VIFs resulting from a collinearity test are equal to or lower than 3.3, the model can be considered free from common method bias (Kock, 2015). Hence our VIFs values in Table 3 suggest that our model is free from CMB, collaborating with Ahakwa et al (2021b) and Ahakwa et al (2021c). Table 4 and Table 5 present the discriminant validity, which signifies the degree to which the measures do not reflect other variables.…”
Section: Measurement Model Assessmentmentioning
confidence: 93%
“…In assessing the overall R 2 of the model, local business, local employment, and LED policy explained 40.5% of the total variance in poverty reduction; thus, R 2 = .405 is greater than the minimum value of .26 suggested by Cohen (1988, see Table 9). This means the overall model of the research was substantive, thus resulting in robust results, collaborating with those of Ahakwa et al (2021aAhakwa et al ( , 2021d and Quagraine et al (2021). According to Korankye et al (2021) and Ying et al (2021), a Q 2 value more than 0 means the research model is higher in its predictive relevance.…”
Section: Testing For the Mediation Role Of Local Employmentmentioning
confidence: 76%
“…Asanov et al [12] found out that 92% of the respondents involved in the study own televisions in their homes, hence they find the television to be of high educative value. A study by Ahakwa, Yang, Tackie and Bankole [13] also revealed that television advertisement has the greatest impact on customer purchase decision and was statistically significant at p< 0.01. The findings of this study are also similar to those of a study conducted by Qader, Hamza, Othman, Anwer, Hamad, Gardi, & Ibrahim, [14], where radio advertisements were found to have beneficial influence on the consumers.…”
Section: Media Source Index Scores Showing Level Of Educative Value C...mentioning
confidence: 94%